The migration of ASEAN's worker to Japan: The impact to the social, culture and politic of Japan - Harun, Azhar; Saad, Shafee (Info Invest, Bulgaria, 2013)
The research will analyze the causes and consequences of the recent dramatic increases of migration from Malaysia and selected ASEAN countries (Thailand and Philippine) to Japan. The research aims at learning some general characteristics of the migrations, and linking them to theoretical explanations of migration and its place in the process of globalization. The research main question is, how do Malaysian and selected ASEAN countries migrants enter to work in Japan both legally and illegally? And what are the possible consequences for the receiving countries, in terms of social, cultural and political change? To answer these these questions, the researcher have to do some field research both in Japan as a host country and in Malaysia and selected ASEAN countries (Thailand and Philippine) as a home country. Three equation has form as hypothesis to answer these question.The output of the study shown that the largest number of ASEAN country's emigrants, will be created more social problem and also affected the culture changed to the Japanese society than the smaller number of ASEAN country's emigrants.